Analisis Realita Pandemi Indonesia Dalam Film Hari Yang Dijanjikan - Nuril Anggraini; Sumaina Duku; Jawasi (CV. ITTC INDONESIA, 2024)
Film, as a means of mass communication, has an important role in conveying messages to a wide audience in the current digital era. Not just a form of entertainment, films are also artistic and cultural expressions that reflect social and cultural realities and have a significant impact on viewers through the messages they convey. The research entitled Analysis of the Reality of the Indonesian Pandemic in the Film The Promised Day aims to analyze how the film The Promised Day by Fajar Bustomi depicts the reality of the COVID-19 pandemic in Indonesia. The research approach used is a qualitative approach with a type of descriptive research that focuses on analyzing the meaning contained in the film. Analysis was carried out on film scenes using Roland Barthes' semiotic analysis technique, paying attention to the meaning of denotation, connotation and myth implied in each scene. The data collection technique begins with making observations. In the context of the research, the initial stage involved selecting texts and images related to the film